A REVIEW ON THE ANTIPARASITIC DRUG IVERMECTIN FOR VARIOUS VIRAL INFECTIONS AND POSSIBILITIES OF USING IT FOR NOVEL SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS 2: NEW HOPE TO TREAT CORONAVIRUS DISEASE-2019 - JABEEN, TALHA; KHADER, MOHD ABDUL; JABEEN, SHAYESTHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The novel coronavirus infection has spread all over the world. With no specific drug or vaccine, the process of “drug repurposing” becomes a feasible solution. As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has 80% sequence similarity with the SARS-CoV, the nuclear import inhibitor “Ivermectin” (IVM) has recently been studied as a possible treatment option for coronavirus disease-2019 (COVID-19). The article aims to provide a review on structure and immunogenicity of SARS-CoV-2, indications of IVM for viral diseases, its possible mechanism on COVID-19 with a brief discussion on IVM structure, pharmacokinetics, adverse drug reactions, drug interactions, and contraindications. Further, we made possible comparisons of IVM with solidarity trial drugs and analyzed its major advantages, limitations and gave necessary recommendations for its use in future in vivo studies in the treatment of COVID-19.